If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = (-2)(b + -3) + 8 Reorder the terms: 24 = -2(-3 + b) + 8 24 = (-3 * -2 + b * -2) + 8 24 = (6 + -2b) + 8 Reorder the terms: 24 = 6 + 8 + -2b Combine like terms: 6 + 8 = 14 24 = 14 + -2b Solving 24 = 14 + -2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2b' to each side of the equation. 24 + 2b = 14 + -2b + 2b Combine like terms: -2b + 2b = 0 24 + 2b = 14 + 0 24 + 2b = 14 Add '-24' to each side of the equation. 24 + -24 + 2b = 14 + -24 Combine like terms: 24 + -24 = 0 0 + 2b = 14 + -24 2b = 14 + -24 Combine like terms: 14 + -24 = -10 2b = -10 Divide each side by '2'. b = -5 Simplifying b = -5
| -8*10-10y=80 | | -t+5=y-19 | | 0.52+0.34t=3.59t-1.43 | | 4(z-2)+z=(-13) | | -4(3+5n)-6(-4n+4)=-12 | | f(x+5)=x^2+10x+25+7x+35+7 | | 0.9y-0.5y=4.4 | | -8x-10y=80 | | X+5=-7 | | 24.5+(-45.5)= | | 1/4[4-4x]=10+2(-4) | | 2y+x=36 | | 4x-10+20=90 | | 3x-12-4x+12=x+3-(x-6) | | y+18=37 | | 1/4(4-x)=10+2(-4) | | X^2+2Y=16 | | 5(x-6)+2x=7(x+2)-44 | | 3(2x-4)+7=13 | | 13z-31=9 | | J=H-Hsy | | 5h-26=18 | | 4y+9-7y=(-6) | | 7(w+5)=6w-4 | | 6x+30(x-12)=2(x-1.5) | | 8n+2=90 | | 6x+10-3x=-2 | | 4x+3(4+x)=-9 | | (6x+4)+(15-7)= | | 11z+4z^2+10z^2= | | 265=(x+5)(3x+5) | | 137=5x+6(-3x+12) |